Responsive biomaterials for therapeutic strategies of hepatocellular carcinoma - Liao, Xun; Zhou, Junxiu; Feng, Liang; Wang, Lian; Wu, Hong; Jiang, Li; Jia, Yuanyuan; Wu, Qingbin; Shen, Shu (Frontiers in Bioengineering and Biotechnology, 2025)
Hepatocellular carcinoma (HCC) represents a major global health burden due to its high recurrence and mortality rates. For patients with advanced HCC and compromised liver function, Pharmacotherapy has become the primary approach due to the limited efficacy of conventional treatments (e.g., surgical resection/ablation). Nevertheless, traditional anti-tumor agents suffer from poor target selectivity, systemic toxicity, and the emergence of drug resistance. To overcome these challenges, stimuli-responsive biomaterials have been developed as innovative strategies to improve HCC management. These advanced materials enable precise spatiotemporal control of drug delivery and release, thereby enhancing therapeutic efficacy while reducing side effects. This review provides a systematic overview of stimuli-responsive biomaterials, classified based on their responses to endogenous cues (e.g., pH, enzymes, and redox conditions) and exogenous stimuli (e.g., light and magnetic fields). These materials show great potential in overcoming biological barriers in HCC therapy and enhancing drug delivery efficiency, thereby paving the way for future clinical applications. By analyzing recent advances, this review highlights the potential of stimuli-responsive biomaterials in advancing therapeutic strategies for HCC. Integrating these materials into HCC therapy may significantly enhance patient outcomes and revolutionize existing treatment paradigms.